Simulation-enabled design and analysis of globe valve - Al-Amin, N.A.-B.M.N. (IOP Publishing Ltd, 2021)
Globe valves serve many purposes in oil and gas facilities as a tool to control fluid flow in pipelines. However, older designs of globe valves suffer many problems and faults, mainly from valve leakage and valve passing. In mitigating these problems, this paper will improve the design of a globe valve to enhance its fluid flow performance and reduce the pressure difference value throughout the valve. The improvements on the valve will be validated from the original design with the help of Computational Fluid Dynamics (CFD) and Finite Element Analysis (FEA). The project concluded that the improved valve design performs better than the original design in all aspects except in terms of valve passing at the contact seal between the seat and the disk in a fully closed position. Implementation of smart sensors and prototyping will be explored in future studies. Â© 2021 Institute of Physics Publishing. All rights reserved.